The Development of The Brain and Spinal Cord and The Anatomy of The Nerves That Emerge from Them - Tolibova Shirin Jonibekovna; Xusanov Shamshod (Scientific Trends, 2026)
This academic article comprehensively reviews the embryonic development and anatomy of the central and peripheral nervous systems, including the brain, spinal cord, and their emerging nerves. It details the process of neurulation, differentiation of brain vesicles, spinal cord segmentation, and the crucial role of neural crest cells in forming the peripheral nervous system. Furthermore, it elucidates the formation, plexuses, structural composition, and functional significance of cranial and spinal nerves. The article outlines the molecular and genetic control mechanisms and key signaling pathways involved in nervous system development. It also emphasizes the clinical implications of developmental disorders and their importance in medicine, highlighting the relevance of deeply understanding this complex biological system in neurology and medical practice.
Keywords: Nervous system, Neurulation, Brain, Spinal cord, Neural crest, Cranial nerves, Spinal nerves, Neuroembryology.